2021
DOI: 10.1101/2021.11.25.469847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Centripetal nuclear shape fluctuations associate with chromatin condensation towards mitosis

Abstract: The cell nucleus plays a central role in several key cellular processes, including chromosome organisation, replication and transcription. Recent work intriguingly suggests an association between nuclear mechanics and cell-cycle progression, but many aspects of this connection remain unexplored. Here, by monitoring nuclear shape fluctuations at different cell cycle stages, we uncover increasing inward fluctuations in late G2 and early mitosis, which are initially transient, but develop into instabilities that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The apparent tension of the nucleus, estimating σ N or σ 0 is around 10 −6 N/m in nuclear shape fluctuations experiments (Chu et al, 2017; Introini et al, 2021), but this value is an underestimation of the actual tension, since it is affected by excess flickering due to transient deformations of active origin (decreasing the effective tension with respect to the actual mechanical tension). We can assume that this value is a lower bound for the real mechanical tension σ 0 .…”
Section: Model Ingredientsmentioning
confidence: 98%
See 1 more Smart Citation
“…The apparent tension of the nucleus, estimating σ N or σ 0 is around 10 −6 N/m in nuclear shape fluctuations experiments (Chu et al, 2017; Introini et al, 2021), but this value is an underestimation of the actual tension, since it is affected by excess flickering due to transient deformations of active origin (decreasing the effective tension with respect to the actual mechanical tension). We can assume that this value is a lower bound for the real mechanical tension σ 0 .…”
Section: Model Ingredientsmentioning
confidence: 98%
“…Additionally, in yeast, the fraction of q of nuclearly-localized to cytoplasmically localized proteins is about 1/2 (Kumar et al, 2002). However, since this factor is a major determinant of the NC volume ratio, and we find ratios that are about 0.2, we conclude that this factor must be smaller in mammalian cells. The apparent tension of the nucleus, estimating σ N or σ 0 is around 10 −6 N/m in nuclear shape fluctuations experiments (Chu et al, 2017; Introini et al, 2021), but this value is an underestimation of the actual tension, since it is affected by excess flickering due to transient deformations of active origin (decreasing the effective tension with respect to the actual mechanical tension). We can assume that this value is a lower bound for the real mechanical tension σ 0 . We assume that cytoskeletal forces are compressive, in line with the recent literature (but we have also considered the opposite case, see below).…”
Section: Model Ingredientsmentioning
confidence: 98%
“…Looking at the flickering of the nucleus, i.e., the changes in the nucleus' contour on the time scale of seconds, Chu et al [36], were able to quantify the mean square amplitude of the fluctuations and showed that this measure correlates with cell cycle stage. Quantitative analysis of nuclear flickering can also yield NE properties such as the NE bending modulus [37].…”
Section: Comparison Of Shape Descriptorsmentioning
confidence: 99%